HoBi-like pestivirus infection in an outbreak of bovine respiratory disease - Hoppe, Ingrid Bortolin Affonso Lux [UNESP]; Souza-Pollo, Andressa de [UNESP]; Medeiros, Andréa Souza Ramos de [UNESP]; Samara, Samir Issa [UNESP]; Carvalho, Adolorata Aparecida Bianco [UNESP] (Elsevier, 2019)
HoBi-like is an emerging pestivirus of the family Flaviviridae detected in cattle herds and biological products of bovine origin in many parts of the world, causing disease similar to that observed in bovine viral diarrhea virus (BVDV) infections. In this study we reported the detection of HoBi-like pestivirus in an outbreak of respiratory disease in calves from Brazil, seropositive for viruses of the bovine respiratory disease complex (BRDC). Thus, serum samples and nasal swabs were collected from calves up to one year old, presenting or not clinical signs of respiratory disease. Serum samples were submitted to virus neutralization test (VNT) for BVDV-1, BVDV-2, bovine herpesvirus-1 (BoHV-1), bovine respiratory syncytial virus (BRSV) and bovine parainfluenza-3 (BPIV-3). These samples were also tested for the presence of pestiviruses (BVDV-1, BVDV-2 and HoBi-like) and BoHV-1 by RT-PCR and PCR, respectively. Nasal swabs were analyzed by RT-PCR for pestiviruses, BRSV and BPIV-3. VNT results showed high serological prevalence and a wide range of antibodies titers, for all viruses studied, in calves of different age groups. The RT-PCR amplified the 5′UTR and E2 regions of pestiviruses of four calves, from both nasal swabs and serum samples, which sequencing identified the HoBi-like pestivirus. This is the first detection of HoBi-like in nasal secretions of calves in an outbreak of respiratory disease in Brazil, along with the serological detection of other respiratory viruses. We concluded that HoBi-like pestivirus should be considered as part of the BRDC, as a differential diagnosis, to take correct measures of control and prophylaxis.
Keywords: Calves; Nasal swabs; Pestiviruses; Phylogeny; Respiratory viruses; Virus neutralization test